2003
DOI: 10.1021/ja021288q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monoglucosylated High-Mannose-Type Dodecasaccharide, a Putative Ligand for Molecular Chaperone, Calnexin, and Calreticurin

Abstract: Convergent and stereoselective synthetic routes to Man9GlcNAc2 (1b), alpha-Glc1M9GlcNAc2 (2b), and its stereoisomer beta-Glc1M9GlcNAc2 (3) were established. Interaction analysis of 2b with CRT was measured by 1H NMR spectroscopy, and the first NMR-based evidence for the specific binding of CRT to 2b was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 133 publications
(53 citation statements)
references
References 18 publications
1
52
0
Order By: Relevance
“…The synthesis of high mannose-type oligosaccharides, Man 9 GlcNAc 2 and its analogues, has been extensively explored (11,(32)(33)(34)(35)(36)(37) by using a convergent approach that is generally more concise and efficient. The one-pot programmable relative reactivity value (RRV) assay (14) revealed that thioglycoside disaccharide building block 10 (RRV ϭ 790) is less reactive than compound 11 (RRV ϭ 3638), 15 (RRV ϭ 3137), and 18 (RRV ϭ 4398).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of high mannose-type oligosaccharides, Man 9 GlcNAc 2 and its analogues, has been extensively explored (11,(32)(33)(34)(35)(36)(37) by using a convergent approach that is generally more concise and efficient. The one-pot programmable relative reactivity value (RRV) assay (14) revealed that thioglycoside disaccharide building block 10 (RRV ϭ 790) is less reactive than compound 11 (RRV ϭ 3638), 15 (RRV ϭ 3137), and 18 (RRV ϭ 4398).…”
Section: Resultsmentioning
confidence: 99%
“…Since the achievement of the total synthesis of high-man- nose-type glycans, [18][19][20] various substrates for UGGT1 have been developed taking advantage of fully chemical synthesis (Fig. 2).…”
Section: Non-proteinic Substratesmentioning
confidence: 99%
“…High-mannose-type glycans are known to interact with a variety of proteins, such as chaperones, lectins, glycosidases, glycosyltransferases, cargo-receptors, and ubiquitin ligases, playing critical roles in the "quality control" of glycoproteins. We have completed the synthesis of most of the high-mannose-type glycans that exist in the ER (13,14,15,16). Tetrahedron, 2006, 62, 8262), and these compounds are under current use as probes to investigate various protein-carbohydrate interactions in glycoprotein quality control (vide infra).…”
Section: A Prefacementioning
confidence: 99%